(Re)interpretations by teachers of the national geography curriculum for primary education in Portugal - Martins, Maria Felisbela (2011)
In Portugal, the Currículo Nacional do Ensino Básico [National Curriculum for Primary Education] was published in 2001. This document reorganises primary level education from a curricular point of view. It is a key reference document for curricular management in Portuguese schools and outlines guidelines for the whole set of educational experiences as well as the core and specific skills that students are to develop in each subject or subject area. Since the implementation of this curriculum reorganisation, working documents have been produced by the Geography Department of the Faculty of Arts of the University of Porto, reflecting the interpretation of documents issued by the Ministry of Education and providing guidelines regarding teacher training in this subject area. These documents were shared among students, future teachers and also trainee supervisors during training sessions. Centred on issues concerning the National Curriculum for Primary Education and Curriculum Guidelines for Geography, this paper aims to present not only the reasons that led the authors of the Geography Curriculum to provide certain options, but also the (re) interpretations made by Geography teachers who graduated from the Faculty of Arts of the University of Porto as regards the fulfilment of the prescribed curriculum at national level, that is, in their professional teaching practice.